Emilio Peral Vega. Pierrot/Lorca: White Carnival of Black Desire. London: Tamesis, 2015. - Enrique Álvarez (Studies in 20th & 21st Century Literature, 2018)
Review of Emilio Peral Vega. Pierrot/Lorca. White Carnival of Black Desire. London: Tamesis, 2015.
Keywords: Spanish Literature; Queer; Lorca